Petalidium konkiepense (Acanthaceae), a new species from Namibia - Swanepoel, Wessel; van Wyk, Abraham E. (Phytotaxa, 2023)
Petalidium konkiepense, here described as a new species, is only known from the Gariep Centre of Plant Endemism in southern Namibia, where it grows on arid hillsides and along drainage lines. Diagnostic morphological characters for P. konkiepense include the rigid, cylindrical distal stems (quadrangular when young), grey or dark brownish grey bark (white to cream when young), densely puberulent vegetative parts with widely spaced robust glandular and eglandular trichomes, and the oblanceolate leaves with prominent midrib and principal lateral veins. A comparison of some of the more prominent features to differentiate Petalidium konkiepense from its morphologically most similar relatives, P. linifolium and P. cymbiforme, is provided. Based on IUCN Red List categories and criteria, a conservation assessment of Endangered under criteria B1 is recommended for the new species.